Strategic Opportunism: What Works in Africa Twelve Fundamentals for Conservation Success - Huntley, Brian John (SpringerBriefs in Environmental Science, 2023)
This open access book. provides a synthesis of six projects, across ten countries, each of which have been sustained for two or more decades, and which illustrate how success can be achieved regardless of systems of governance, of a nation's wealth, or of culture. Detailed narratives are presented on the key personalities that have conceived, conducted and concluded long-term projects: personal stories of vision, failure, frustration and persistence ultimately leading to success. The case studies vary widely in their geography and goals. The single-handed commitment to re-discover the last surviving populations of Giant Sable in the miombo woodlands of central Angola, through the capture, translocation and establishment of robust breeding herds of this magnificent antelope, contrasts with the massively funded, three-decade programme with over one hundred participants that reversed the annual loss to predation by feral cats of 455 000 seabirds from a sub-Antarctic island. Similarly, the foresight of Zimbabwean and Namibian ecologists to place rural communities at the centre of conservation programmes by giving value to wildlife populations and benefits to local people, transformed a land degradation problem to a socio-ecological solution. Across ten countries, building capacity in botanical collection, documentation and herbarium management expanded into a global project to place the knowledge base of Africa's flora onto an electronic data system accessible to researchers and conservation planners in even the most remote corners of the continent. None of these projects enjoyed immediate results. Each required leadership skills that combined vision, a generosity of spirit, fortuitous timing and the exploitation of unexpected opportunities.